Cross-National comparison of antiepileptic drug use: Catalonia, Denmark and Norway, 2007-2011 (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Antiepileptic drug  (AED)consumption has increased in recent years mainly from those AEDs marketed since 1990. The purpose is to describe and compare AED consumption in Catalonia, Denmark and Norway.Methods: Population-based descriptive study set in the outpatient healthcare sector. Data were retrieved from the Norwegian Prescription Register, Danish Register of Medicinal Product Statistics and DATAMART® in Catalonia, for 2007-2011.We calculated defined daily doses/1000 inhabitants/day (DID), by age and gender. AEDs were defined according to the Anatomical Therapeutic Chemical classification (N03A). We reviewed the population covered by the databases, the drug data source and the definition of outpatient healthcare sector to compare the results across the three settings.Results: Total AED use steadily increased over the study period in the three settings. In 2011, consumption was highest in Catalonia (15.20 DID), followed by Denmark (15.06 DID) and Norway (14.24 DID). The “other AEDs” (N03AX) subgroup represented 60% of all AED use. The N03A pattern by gender did not differ across the three settings. Marked differences by age and gender appeared when studying lamotrigine, topiramate, gabapentin, pregabalin and levetiracetam.  Differences among the databases were mainly in the definition of outpatient healthcare setting.Conclusions: There was a rapid increase in “other AEDs” in all three settings. Although we did not have information on the indication for the use of AEDs, the drug data source, population coverage of the database and definition of the healthcare setting helped us interpret the results.